TINDAK TUTUR DAN FUNGSI TUTURAN EKSPRESIF DALAM ACARA NIH KITA KEPO DI TRANS TV: SUATU KAJIAN PRAGMATIK - Safira, Fatma Eka (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
The research to describe the use of speech acts conveyed by speakers to interlocutors in the Nih Kita Kepo program on Trans TV in the forms of speech acts of locua, illocution, perlocution, and expressive speech. The method used in this research is descriptive qualitative method. The data collection technic used in this study was the observation, record and note technique. The results of this study are data in the form of types of speech acts found in the Nih Kita Kepo program on Trans TV. Based on the results of this analysis, it can be concluded that at the Nih Kita Kepo program on Trans Tv there are types of speech acts locus, illocution, perlocution and expressive speech functions which consist of expressive speech saying congratulations, thanks, criticizing, complaining, blaming, praising, apologize, and insinuate.